PENGARUH SISTEM PENGENDALIAN INTERN, KEPATUHAN, DAN PEMBERIAN TAMBAHAN PENGHASILAN BERSYARAT (TPB) TERHADAP PERILAKU ETIS PEGAWAI (Studi Kasus Pada Badan Pengelolaan Pendapatan Daerah Pemerintah Kabupaten Jayapura) - Andhika Dwi Abriyanti; Siti Rofingatun; Mariolin A. Sanggenafa (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2020)
This study aims to determine the effect of internal control, compliance, additional income conditional on the ethical behavior of employees of the revenue management agency in Jayapura district. This research is correlation research or relationship, with the unit of analysis being studied are employees who work in the BAPENDA office with a total sample of 40 employees. The questionnaire was tested for validity and reliability before testing the research data, the test equipment used in this study used the classical assumption test which included the normality test for linearity heteroscedasticity and the linearity test data analysis method used was multiple linear regression analysis using the statistical analysis tool SPSS 25.The results ofthis study indicate that the Internal Control System variable does not have a significant effect on employee ethical behavior, while the Compliance and SupplementaryConditional variables have a significant effect on employee ethical behavior. Variables Internal control, compliance and management compensation together (simultaneous) have a positive and significant effect on employee ethical behavior.